A Review on Congenital Tuberculosis (Med Phoenix, 2017)
Background: Congenital tuberculosis is defined as infection acquired to a newborn from infected mother by Mycobacterium tuberculosis bacilli during the intrauterine period or during normal birth. Though tuberculosis infection is very common all over the world, congenital tuberculosis is rare and mortality is 50%. Nonspecific symptoms in congenital tuberculosis and difficulties encountered in the diagnosis of tuberculosis in general, make it difficult to reach a final diagnosis so congenital tuberculosis is generally known clinically during the first postnatal month. Maternal tuberculosis is common but congenital tuberculosis is rare and fatal. Also the clinical features are not specific but diagnosis is difficult. So screening of all pregnant ladies can help in early diagnosis and prevention of congenital tuberculosis.Methods: This article has been produced by analyzing various publications since 1998 till date, and by using search gear, pub med, hinari and google.Result: Around 350 cases have been reported so far from different part of the world. There is paucity of data from our part of world.Conclusion: The difficulties in diagnostic and therapeutic conduct of this disease, which are of great interest to public health, points to the need to develop specific protocols. MED Phoenix Volume (1), Issue (1) July 2016, Page: 19-22